The Relationship Between the Sense of Professional Belonging and Perceptions of Spirituality and Spiritual Care Among Turkish Midwifery Students - Cangöl, Eda (Journal of religion and health, 2024)
This study examined the relationship between the sense of professional belonging and perceptions of spirituality and spiritual care among midwifery students. This cross-sectional study’s sample included 194 third- and fourth-year midwifery students associated with the Faculty of Health Sciences at two universities in western Turkey. Data were collected using web-based surveys. The results indicate a positive relationship between total scores on the Midwifery Belonging Scale and scores on the Spirituality and Spiritual Care Rating Scale. As the students’ spirituality and spiritual care perceptions increased, their feelings of professional belonging as midwives also increased. Therefore, including the concepts of spirituality and belonging in the midwifery curriculum can increase students’ spiritual perceptions and sense of professional belonging, thereby enhancing the quality of the care they ultimately provide.